New program for identification of child maltreatment in emergency department: preliminary data. Issue 1 (December 2016) - Milani, Gregorio; Vianello, Federica; Cantoni, Barbara; Agostoni, Carlo; Fossali, Emilio
Abstract Early detection of child maltreatment in pediatric emergency department is one of the most important challenges for the Italian and European medical care system. Several interventions have been proposed, but results are often unquantifiable or inadequate to face this problem. We promoted an educational program and built up an interdisciplinary team to improve the identification and management of maltreated children. Aim of this study is to report preliminary results of these interventions. Meetings structured with lecture-based teaching and case-based lessons were focused on identification and management of maltreatment cases. An interdisciplinary team with forensic physicians, dermatologists, orthopedics, radiologists, gynecologists, oculists, psychologists and psychiatrics, was created to manage children with suspected diagnosis of maltreatment. We analysed the characteristics of subjects diagnosed after these interventions and their number was compared with the one in the two previous years. An increased rate of diagnoses of 16.9 % was found. Results of the reported program are encouraging, but many efforts are still mandatory to improve the child maltreatment identification in emergency departments.